Biochemical and molecular identification of Enterococcus spp. from red pitaya - Ong, Yien Yien; Tan, Wen Siang; Mohamad, Rosfarizan; Sieo, Chin Chin; Tey, Beng Ti (Elsevier, 2014)
Red pitaya is a popular fruit worldwide due to its unique appearance and high nutrient contents. Many studies about the nutritional content and the physico-chemical characteristics of red pitaya have been performed but microorganisms that occurred naturally in the fruit remained unknown. Therefore, this study was conducted to characterize the enterococci present in red pitaya. Enterococci were isolated from red pitaya fruit and characterized with biochemical tests, randomly amplified polymorphic DNA (RAPD) and restriction fragment length polymorphism (RFLP) of the 16S rDNA region. A total of 30 bacteria were isolated from red pitaya, of which 20 isolates were confirmed as enterococci, genus Enterococcus. 13 isolates were further confirmed as Enterococcus casseliflavus and 7 were identified as Enterococcus gallinarum.